The Montefiore-Einstein Rigidity Scale-Revised (MERS-R): Development, administration, reliability, and validity in child and adult Autism Spectrum Disorder (ASD). (March 2022) - Taylor, Bonnie P.; Liu, Jianyou; Mowrey, Wenzhu; Eule, Eckhart; Bolognani, Federico; Hollander, Eric
Abstract: Background: Rigidity contributes to severity and functional impairment in autism spectrum disorder (ASD). There is an unmet need for a valid, reliable, and sensitive outcome measure to assess rigidity in ASD. Objective: To develop and validate the Montefiore-Einstein Rigidity Scale-Revised (MERS-R) to assess the Behavioral Rigidity Domain (BRD), Cognitive Rigidity Domain (CRD), and Protest Domain (PD). Materials and methods: The MERS-R was administered to 93 individuals with ASD (children and adults, high and low IQ) at baseline, Week 2, and Week 12. Internal consistency was assessed for domain scores, Total Rigidity Composite (TRC = BRD + CRD), and Total Composite (TC = BRD + CRD + PD) with Cronbach's α. Intraclass correlation coefficients (ICCs) assessed test-retest reliability from baseline to weeks 2 and 12. Pearson's correlations assessed the relationship between the MERS-R and age, sex, and IQ. Convergent validity assessed the correlation of MERS-R scores to the Children's Yale-Brown Obsessive-Compulsive Scale-ASD (CY-BOCS-ASD). Results: Good internal consistency was demonstrated for the BRD, PD, TRC and TC (Cronbach's α = 0.83, 0.88, 0.82, and 0.89, respectively) and adequate internal consistency for the CRD (α = .72). Good or excellent test-test reliability was demonstrated over two weeks (ICC: 0.66─.79), and fair or good reliability over 12 weeks (ICC: 0.56–66). MERS-R scores did not differ by age, sex, or IQ (p: 0.16─.99) with the exception that higher PD scores were associated with younger age (correlation = −0.25, p = 0.01). Significant convergent validity was demonstrated between all MERS-R scores and the CY-BOCS-ASD (p < 0.0001). Discussion: The MERS-R demonstrated internal consistency, test-retest reliability, convergent validity and applicability to autistic children and adults of different sexes and IQ levels. It is a valid, sensitive, and reliable instrument to measure behavioral and cognitive rigidity in ASD.